The Effect of a Combination of Binaural Beat Music and Rose Aromatherapy on Maternal Anxiety: Pengaruh Kombinasi Musik Binaural Beat dan Aromaterapi Mawar terhadap Kecemasan Ibu Bersalin - Hartato, Febrilianti; Susanti, Eva; Sari, Wenny Indah Purnama Eka (Napande: Jurnal Bidan, 2024)
Background: Anxiety is physiological during labor, resulting in increased sympathetic nerve activity and increased catecholamines secretion. Excessive catecholamine secretion reduces blood flow to the placenta, limits oxygen supply, and slows uterine contractions, which can slow down labor. To reduce the risk of complications, anxiety must be addressed. One of them is the provision of binaural beat music therapy and rose aromatherapy. Objective: to determine the effect of alpha pattern beat binaural music therapy and rose aromatherapy on anxiety levels in laboring women in active phase I. Methods: The design of this study was a quasi-experimental Two-group of pretest-posttest design. The sample in this study consisted of 60 respondents using a simple random sampling technique. The instrument used in this study was the STAI Questionnaire (Stait-Trait Anxiety Inventory). The data analysis technique used the Chi-Square test. Results: Obtained p-value of 0.02<0,005. Hence, there was an effect of the combination of alpha binaural beat music therapy and rose aromatherapy on the level of labor anxiety in the first stage of the active phase. Conclusion: The combination of alpha pattern binaural beat music therapy and rose aromatherapy affects reducing the level of labor anxiety in the first stage of the active phase.